Environmental pollution due to gaseous emissions during non-ferrous extraction processes - Ghosh, Manojit; Banerjee, P. S.; Ray, H. S. (Russian journal of non-ferrous metals, 2014)
All steps in extraction of primary nonferrous metals can be highly polluting because of emission of air pollutants as green house gases this paper discusses this subject and the measures that can minimise pollution. It focuses mainly on aluminium and the base metals however the countermeasures discussed are often for general application.